Integrating Volcanic Hazard Data in a Systematic Approach to Develop Volcanic Hazard Maps in the Lesser Antilles - Lindsay, Jan M.; Robertson, Richard E. A. (Frontiers in Earth Science, 2018)
We report on the process of generating the first suite of integrated volcanic hazard zonation maps for the islands of Dominica, Grenada (including Kick ‘em Jenny and Ronde/Caille), Nevis, Saba, St. Eustatius, St. Kitts, Saint Lucia and St Vincent in the Lesser Antilles. We developed a systematic approach that accommodated the range in prior knowledge of the volcanoes in the region. A first-order hazard assessment for each island was used to develop one or more scenario(s) of likely future activity, for which scenario-based hazard maps were generated. For the most-likely scenario on each island we also produced a poster-sized integrated volcanic hazard zonation map, which combined the individual hazardous phenomena depicted in the scenario-based hazard maps into integrated hazard zones. We document the philosophy behind the generation of this suite of maps, and the method by which hazard information was combined to create integrated hazard zonation maps, and illustrate our approach through a case study of St. Vincent. We also outline some of the challenges we faced using this approach, and the lessons we have learned by observing how stakeholders have interacted with the maps over the past ~10 years. Based on our experience, we recommend that future map makers involve stakeholders in the entire map generation process, especially when making design choices such as type of base map, use of colour and gradational boundaries, and indeed what to depict on the map. We also recommend careful consideration of how to evaluate and depict offshore hazard of island volcanoes, and recommend computer-assisted modelling of all phenomena to generate more realistic hazard footprints. Finally, although our systematic approach to integrating individual hazard data into zones generally worked well, we suggest that a better approach might be to treat the integration of hazards on a case-by-case basis to ensure the final product meets map users’ needs. We hope that the documentation of our experience might be useful for other map makers to take into account when creating new or updating existing maps.